(untitled) (International Journal of Built Environment and Sustainability, 2023)
With an increased demand for housing, mass housing focuses on speed and economic benefit and standardizes. Different user groups cannot find answers to some of their physical and social needs in this housing and its surroundings. This circumstance generates socially unsustainable regions. From this point of view, the study seeks answers to the questions "What is the social sustainability satisfaction level of the users?" and "Is there a statistically significant difference between the social sustainability satisfaction levels and the different characteristics of the users in the existing mass housing areas?" So, the study reveals the criteria necessary for ensuring social sustainability, defines the level of satisfaction with the fulfillment of these criteria, and determines the statistical difference in satisfaction based on resident characteristics. The link between housing and social sustainability was evaluated using the criteria of social equity and sustainability of community. 87 residents filled out the questionnaire form in a mass housing complex in Istanbul. Researchers used descriptive statistics, the Mann Whitney-U, and the Kruskal-Walis tests to define the statistical difference between social sustainability parameters and the demographic characteristics of the residents. The analysis revealed that inclusion and spatial diversity satisfaction on the housing scale were at the highest level and satisfaction with the Participation criteria was at the lowest level in ensuring social sustainability. The results of the Mann-Whitney U and Kruskal-Wallis tests are as follows: The spatial diversity satisfaction differed in terms of education, economic status, housing type, and length of residence; the social diversity satisfaction differed in terms of gender and age; and the accessibility sub-criterion differed in terms of gender. Only social interaction satisfaction differed by gender, education, and employment status among the sustainability of community criteria. The satisfaction of inclusion, security, community stability, sense of place, and participation were unaffected by demographic characteristics.